Extract of Glycyrrhiza Glabra Root Attenuates Nociception in Experimental Pain Models: The Role of Bkca Channels [Extracto de Raíz de Glycyrrhiza Glabra Atenúa la Nocicepción en Modelos Experimentales de Dolor: El Rol de Los Canales Bkca] - Martinez-Salinas, J; Rios-Ramirez, M (MS-Editions, 2022)
The aim of this study was to evaluate the functional interaction of Glycyrrhiza glabra root extract (GGRE) on the large conductance Ca2+-activated K+ (BKCa) channels expressed in the peripheral nervous system by using nociception and inflammation models in rodents in vivo. Besides toxicity studies and open field tests, nociception and inflammation tests were performed on rodents. Different doses of GGRE were given orally to rats and mice. Naloxone, indomethacin, morphine, NS1619 and iberiotoxin (IbTX) were administered. GGRE had both anti-nociceptive and anti-inflammatory activity in rats and mice. GGRE exhibited an analgesic effect by decreasing the time-course of the pain threshold or reaction time in some nociceptive tests. Furthermore, GGRE reduced level of pro-inflammatory cytokines, including TNF-α and IL-1β. As a conclusion, GGRE can alleviate the pain sensation of the afferent nerves and can reduce inflammation and associated pain by activating BKCa channels and reducing the levels of TNF-α, IL1β. © 2022, MS-Editions. All rights reserved.